Evaluación de sistemas agroforestales sobre la base de indicadores de sustentabilidad en 5 comunidades de la parroquia Palmira, cantón Guamote, provincia de Chimborazo. - Chacaguasay Apugllon, Edisson Diego (2018)
In this research project was done the evaluation of agroforestry systems, in the communities of Palmira Dávalos, San Francisco, 4 Esquinas, Atapo Santa Cruz 1, Atapo Santa Cruz 2 and Atapo Quichalán, from the Palmira Parish in the Guamote Canton of the Chimborazo Province, for this evaluation were analyzed economic and social environmental indicators, which allowed us to know the living forest and fruit species, through this study to characterize and recommend them the results based of the agroforestry system. For which a standardized scale (judgment value) was constructed that represents the value of the indicators in relation to the current situation. For this reason were defined maximum and minimum ranges, in this case, taking into account the characteristics of the agroforestry systems, a value was assigned:High = 1, Medium = 0.75, Low = 0.50, Very low = 0.25, based on Santiago Sarandon´s methodology. The living forest species studied in these communities are: Lupines (Cytisusmon spesolanum), Lime (Sambucus nigra), Alder (Alnus acuminata), Arrayan (Myrcianthers hopaloides), Mallow (Malva sylvestris), Llinllin (Sennamulti glandulosa) and fruit species are consider: Uvilla (Physalis peruviana L), Blackberry (Rubus galucus), Taxo (Pasiflora tripartita), Capuli (Prunus salicifolia), with percentage of capture of 51% to 80% that is considered an average range of to grab of the species before mentioned, while the species: Yagual (Polylepis racemosa), Black Acacia (Acacia melanoxylon), showed a percentage of capture of 21% to 50%, which represents a low percentage of capture. Using the Santiago Sarandon´s standardized methodology the following results were obtained: environmental dimension = 0.68, economic dimension = 0.70 and in the social dimension 0.69, which shows that agroforestry systems are sustainable in the evaluated dimensions. To calculate the general sustainability, the following formula was applied: IG (General Index) = (S + E + A) / D and the result obtained is 0.69, which shows that there is sustainability in the analyzed area because in the standardization it represents a general index of 2.76 according to the Sarandon´s methodology.